Corner Foam Versus Flat Foam: An Experimental Comparison on Cushion Performance. (5th September 2014) - Ge, Changfeng; Huang, Haoqi
<x xml:space="preserve">Abstract</x> Most cushion structures used in the industry are end caps, edge or corner foam. The bearing area and thickness of the cushioning obtained from cushion curves apply, in principle only, to flat foam because the specimens used to develop the cushion curves are flat foam samples. This study is aimed at finding the difference between the two foams in stress–strain relationship and dynamic impact. A hysteresis cycle compression test, in conjunction with digital image correlation techniques, and a shock cushion test were performed to assess the static stress and strain, energy dissipated and maximum acceleration of flat and corner foams. The study found that the static stress of the corner foam that occurred during the compression testing is 23% higher in average than the flat foam, depending on the compression speed. The shock cushion curve of the corner foam showed a similar pattern as the flat cushion curve but was shifted horizontally to the right as a result of the increased static stress. This study recommends that the conventional cushion curve should be shifted to the right horizontally by about 23–35% in order for a packaging designer to apply it for corner foam. Copyright © 2014 John Wiley & Sons, Ltd.